2019
DOI: 10.1080/08897077.2018.1550466
|View full text |Cite
|
Sign up to set email alerts
|

The State of Substance Use Education in Master of Social Work Programs: A Content Analysis of Course Listings and Faculty Profiles

Abstract: Background: Substance use is currently a pervasive problem among a large proportion of populations served by the social work profession. Several studies have indicated that social workers routinely provide services to clients with direct and indirect substance use needs, making knowledge of substance use interventions and public policies a necessity for social workers to operate effectively in the field. However, despite the regularity of interaction with substance using clients, previous research has suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Faculty members play an important role in preparing students, implementing the simulation activity, debriefing, and evaluating the simulation-based learning activity. Many researchers discussed the importance of training faculty members to teach students about social work practice more effectively (Lundgren, Salas-Wright, Amodeo, Krull, & Alford, 2018; Minnick, 2019) and noting the value of faculty members with clinical practice experience (Berzoff & Drisko, 2015). Lundgren, Salas-Wright, Amodeo, Krull, and Alford (2018) argue that the workforce gap in areas such as addictions can be addressed strategically by training faculty members in these specialized areas.…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…Faculty members play an important role in preparing students, implementing the simulation activity, debriefing, and evaluating the simulation-based learning activity. Many researchers discussed the importance of training faculty members to teach students about social work practice more effectively (Lundgren, Salas-Wright, Amodeo, Krull, & Alford, 2018; Minnick, 2019) and noting the value of faculty members with clinical practice experience (Berzoff & Drisko, 2015). Lundgren, Salas-Wright, Amodeo, Krull, and Alford (2018) argue that the workforce gap in areas such as addictions can be addressed strategically by training faculty members in these specialized areas.…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…Also of note, a review of the literature regarding substance use education in social work showed that there is a large amount of evidence indicating that social work academic programs generally provide students with insufficient instruction on substance use treatment topics, and that social work practitioners are often poorly prepared to deliver substance use treatment services in the field following graduation without extensive post-employment training. 1 , 6 8 This finding additionally strengthens the need for ground-level research regarding how TPDs assess ESWs substance use capacities given the importance of social workers to the mental/behavioral health workforce and the provision of substance use treatment services in NYS.…”
Section: Introductionmentioning
confidence: 60%
“…2 Curriculum development efforts are underway in the United States to expand social work education and training in substance use, 4 an area identified as lacking formal curriculum. 5 Recent intervention models, such as Screening, Brief Intervention, and Referral to Treatment (SBIRT) provide social workers and other health providers with brief, effective tools to address clients engaged in unhealthy substance use. 6,7 These tools are designed specifically for use by social workers and other providers outside of specialty alcohol and other drug treatment, thus increasing the accessibility of SBIRT in various health and behavioral health care settings.…”
Section: Introductionmentioning
confidence: 99%